Lithium ion battery

CN119695240AActive Publication Date: 2025-03-25ZHUHAI COSMX BATTERY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411792051.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-25
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to failure, combustion or explosion when subject to external mechanical action, mainly due to the increase in current collector fracture and internal short circuit.

Method used

Conductive particles are added to the protective layer of the positive electrode sheet, and fluorine solvent is added to the electrolyte to control the average particle size of the conductive particles and the mass content of the fluorine solvent to meet 0.5≤b/k≤15 to enhance the safety performance and circulation performance of the battery.

Benefits of technology

Through the synergistic action of conductive particles and fluorinated solvents, the mechanical strength and conductivity of the battery are improved, the probability of internal short circuit is reduced, and the safety and circulation performance of the battery are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695240A_ABST
    Figure CN119695240A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery which comprises a positive plate, a negative plate, electrolyte and a diaphragm, the positive plate comprises a positive current collector, a positive active layer and a protective layer, the protective layer is arranged on the outer surface of at least one side of the positive current collector, and the positive active layer is arranged on the surface, away from the positive current collector, of the protective layer; the protective layer comprises conductive particles, each conductive particle comprises an inner core and a shell layer arranged on at least part of the surface of the inner core, the inner core comprises an inorganic material, and the shell layer comprises a conductive material; the electrolyte comprises a fluorinated solvent; the lithium ion battery satisfies 0.5 < = b / k < = 15, b is the average particle size of the conductive particles, the unit is [mu] m, k is the mass content of the fluorinated solvent in the electrolyte, and the unit is%. The lithium ion battery has relatively high safety performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a lithium ion battery. Background Art

[0002] At present, lithium-ion batteries with higher energy density and thinner weight are generally obtained by reducing the thickness of the current collector. However, when lithium-ion batteries are subjected to mechanical effects such as external puncture, extrusion or impact by heavy objects, they are prone to failure and even fire, explosion and other safety issues. This is because when the battery is subjected to mechanical damage, it is not only easy to cause the current collector to break, but also the probability of internal short circuits is greatly increased, such as direct contact short circuit between the positive active layer and the negative current collector, direct contact short circuit between the positive current collector and the negative active layer, direct contact between the positive current collector and the negative current collector, etc. At this time, huge current and heat will be generated instantly, causing battery failure and even combustion and fire.

[0003] Therefore, how to improve the safety performance of batteries is an urgent problem to be solved in this field. Summary of the invention

[0004] In view of the above-mentioned defects, the present invention provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet includes a protective layer, and the electrolyte includes a fluorinated solvent. By making the average particle size of the conductive particles in the protective layer and the mass content of the fluorinated solvent in the electrolyte satisfy a special relationship, the battery can have both high safety performance and cycle performance.

[0005] The present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises a positive electrode current collector, a positive electrode active layer and a protective layer, wherein the protective layer is arranged on at least one side surface of the positive electrode current collector, and the positive electrode active layer is arranged on a surface of the protective layer away from the positive electrode current collector;

[0006] The protective layer comprises conductive particles, wherein the conductive particles comprise a core and a shell disposed on at least a portion of the surface of the core, wherein the core comprises an inorganic material, and the shell comprises a conductive material;

[0007] The electrolyte includes a fluorinated solvent;

[0008] The lithium-ion battery satisfies 0.5≤b / k≤15, wherein b is the average particle size of the conductive particles, in μm, and k is the mass content of the fluorinated solvent in the electrolyte, in %.

[0009] Further, the fluorinated solvent includes at least one of fluoroethylene carbonate, ethyl monofluoroacetate, methyl difluoroacetate, ethyl difluoroacetate, methyl trifluoroethyl carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, monofluorobenzene, 1,2-difluorobenzene, p-difluorobenzene, tris(2,2,2-trifluoroethyl) phosphate, bis(2,2,2-trifluoroethyl) phosphonate, 1,2-difluoroethylene, monofluoroethylene, and monofluoropropylene;

[0010] And / or, the inorganic material includes at least one of aluminum oxide, magnesium oxide, titanium oxide, zinc oxide, silicon oxide, boehmite, and cobalt oxide;

[0011] And / or, the conductive material includes at least one of antimony-doped tin dioxide, fluorine-doped tin dioxide, tin-doped indium oxide, and carbon material.

[0012] Furthermore, the mass content k of the fluorinated solvent in the electrolyte is 5 to 30%;

[0013] And / or, the mass content of the conductive particles in the protective layer is 70-98wt%.

[0014] Furthermore, the average particle size b of the conductive particles is 0.05-1 μm.

[0015] Furthermore, the mass content of the shell layer in the conductive particles is 2 to 40%;

[0016] Preferably, the mass content of the shell layer in the conductive particles is 10-30%.

[0017] Furthermore, the diaphragm includes a substrate, a glue layer and a ceramic layer;

[0018] Preferably, the ceramic layer is disposed on at least one side surface of the substrate, and the adhesive layer is disposed on a surface of the ceramic layer away from the substrate;

[0019] Preferably, the surface density p of the ceramic layer is 2 to 6 g / cm 3 .

[0020] Furthermore, the electrolyte also includes a lithium salt, and the lithium salt includes lithium hexafluorophosphate and lithium tetrafluoroborate;

[0021] Preferably, the total mass of the lithium hexafluorophosphate and lithium tetrafluoroborate accounts for 8-20% of the electrolyte;

[0022] Preferably, the mass ratio of lithium hexafluorophosphate to lithium tetrafluoroborate is (10-145):1.

[0023] Furthermore, the thickness h1 of the protective layer is 1 to 10 μm, and / or the thickness h2 of the positive electrode active layer is 30 to 120 μm, and / or the thickness h3 of the positive electrode current collector is 3 to 12 μm.

[0024] Furthermore, the electrolyte also includes additives;

[0025] The additive comprises at least one of vinylene carbonate, propylene sultone, methylene methane disulfonate, 1,3-propane sultone, vinyl sulfate, bis-succinonitrile, adiponitrile, glutaronitrile, hexane trinitrile, ethylene glycol bis(propionitrile) ether, glycerol trinitrile, tetravinylsilane, tris(trimethylsilyl)borate, hexamethyldisilazane, triphenyl phosphite, pentafluoroethoxy cyclotriphosphazene, and 1,3,5-hexane trinitrile;

[0026] Preferably, the mass content of the additive in the electrolyte is 0.1-20%.

[0027] Furthermore, the protective layer also includes a binder;

[0028] The binder comprises at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene and polyethylene oxide;

[0029] Preferably, the mass content of the binder in the protective layer is 2-30wt%.

[0030] The lithium ion battery of the present invention provides a protective layer on the surface of the positive electrode active layer, adds a fluorinated solvent to the electrolyte, and controls the average particle size b of the conductive particles in the protective layer and the mass content k of the fluorinated solvent in the electrolyte to satisfy 0.5≤b / k≤15, so that the conductive particles in the protective layer and the fluorinated solvent in the electrolyte can cooperate and coordinate with each other, thereby effectively improving the safety performance and cycle performance of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A schematic diagram of the structure of a positive electrode sheet of the present invention in one embodiment;

[0032] Figure 2 It is a schematic structural diagram of the positive electrode sheet of the present invention in another embodiment.

[0033] Description of reference numerals:

[0034] 1- Protective layer;

[0035] 2-positive electrode active layer;

[0036] 3- Positive electrode current collector. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] A first aspect of the present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises a positive electrode current collector, a positive electrode active layer and a protective layer, wherein the protective layer is arranged on at least one side surface of the positive electrode current collector, and the positive electrode active layer is arranged on a surface of the protective layer away from the positive electrode current collector;

[0039] The protective layer includes conductive particles, the conductive particles include a core and a shell disposed on at least a portion of the surface of the core, the core includes an inorganic material, and the shell includes a conductive material;

[0040] The electrolyte includes a fluorinated solvent;

[0041] The lithium-ion battery satisfies 0.5≤b / k≤15, wherein b is the average particle size of the conductive particles, in μm, and k is the mass content of the fluorinated solvent in the electrolyte, in %.

[0042] Exemplarily, when k is 15% and b is 0.2 μm, b / k=0.15 / 0.2=0.75.

[0043] Illustratively, b / k is 0.5, 1, 2, 4, 6, 8, 10, 12, 14 or 15.

[0044] Figure 1 is a schematic structural diagram of a positive electrode sheet in one embodiment, Figure 1 In the embodiment, the protective layer 1 is disposed on one side surface of the positive electrode current collector 3 , and the positive electrode active layer 2 is disposed on the surface of the protective layer 1 away from the positive electrode current collector 3 .

[0045] Figure 2 is a schematic structural diagram of a positive electrode sheet in another embodiment, Figure 2 In the embodiment, the protective layer 1 is arranged on both side surfaces of the positive electrode current collector 3 , and the positive electrode active layer 2 is arranged on the surface of the protective layer 1 away from the positive electrode current collector 3 .

[0046] The lithium ion battery in the present invention has high safety performance and cycle performance. This is mainly because when the lithium ion battery is subjected to external mechanical action, the protective layer 1 disposed between the positive electrode active layer 2 and the positive electrode current collector 3 can increase the mechanical strength of the battery structure, especially when subjected to external physical impact, it can protect the battery from being easily broken or damaged. At the same time, the special structure of the conductive particles in the protective layer 1 can not only ensure the safety of the battery, but also provide sufficient conductivity, which can effectively reduce the internal resistance of the battery and make the battery have a higher cycle performance. However, the binding force between the shell and the core in the conductive particles is poor, and it is easy to fall off and separate, which has a negative impact on the safety and cycle performance of the battery. By adding a fluorinated solvent to the electrolyte, the fluorinated solvent can penetrate between the shell and the core in the conductive particles, wherein the stronger electronegativity of fluorine can form a strong hydrogen bond with the core and the shell, and enhance the adhesion between the shell and the core, thereby effectively improving the binding strength between the shell and the core in the conductive particles, thereby ensuring the connectivity of the conductive network, enhancing the conductivity of the material as a whole, and eliminating the negative impact caused by the unstable core-shell structure of the conductive particles.

[0047] Furthermore, after analysis by the inventors, the average particle size of the conductive particles and the mass content of the fluorinated solvent in the electrolyte also have a great influence on the cycle performance and safety of the battery. If the average particle size of the conductive particles is too large, the thickness of the protective layer 1 will be too thick, affecting the cycle performance of the battery; if the average particle size is too small, although it is conducive to achieving a thin coating of the protective layer 1 on the positive electrode current collector 3 to ensure the cycle performance of the battery, the safety performance will be reduced. If the mass content of the fluorinated solvent in the electrolyte is too large, the activity of the binder in the positive electrode active layer 2 will also be enhanced, making it difficult for lithium ions to be deintercalated and degraded, and the cycle will be degraded; if it is too small, it will not be able to form sufficient hydrogen bonds with the core and shell, and thus it will not be able to enhance the bonding strength between the core and shell.

[0048] Therefore, by controlling the average particle size of the conductive particles and the mass content of the fluorinated solvent in the electrolyte to satisfy a specific relationship of 0.5≤b / k≤15, the conductive particles and the fluorinated solvent can work together to comprehensively improve the safety and cycle performance of the battery.

[0049] The average particle size of the conductive particles in the present invention can be obtained by scanning electron microscopy (SEM) testing. Specifically, the conductive particles are subjected to SEM testing, and the conductive particles in three 50 μm*50 μm regions are randomly tested, and the particle sizes of the conductive particles in the three regions are measured respectively, and the average value is taken, which is the average particle size of the conductive particles.

[0050] The present invention does not specifically limit the type of the positive electrode current collector 3, and materials commonly used in the art, such as aluminum foil, can be used.

[0051] The present invention does not specifically limit the types and sources of the inorganic materials, conductive materials and fluorinated solvents, and any commercially available products or products prepared by conventional preparation methods known to those skilled in the art may be used.

[0052] The present invention does not specifically limit the method for manufacturing the lithium-ion battery, and the lithium-ion battery can be manufactured using a common method in the art.

[0053] In a specific embodiment, the fluorinated solvent includes at least one of fluoroethylene carbonate, ethyl monofluoroacetate, methyl difluoroacetate, ethyl difluoroacetate, methyl trifluoroethyl carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, monofluorobenzene, 1,2-difluorobenzene, p-difluorobenzene, tris(2,2,2-trifluoroethyl) phosphate, bis(2,2,2-trifluoroethyl) phosphonate, 1,2-difluoroethylene, monofluoroethylene, and monofluoropropylene.

[0054] When the fluorinated solvent is at least one of the aforementioned multiple specific compounds, the bonding strength between the shell layer and the core can be further enhanced, thereby improving the cycle performance and safety performance of the battery.

[0055] When the fluorinated solvent is a mixture of the aforementioned multiple specific compounds, the present invention does not specifically limit the ratio between the specific compounds.

[0056] In a specific embodiment, the inorganic material includes at least one of aluminum oxide, magnesium oxide, titanium oxide, zinc oxide, silicon oxide, boehmite, and cobalt oxide. In this case, a better protection effect can be achieved and the safety performance of the battery can be improved.

[0057] When the inorganic material is a mixture of the aforementioned multiple specific compounds, the present invention does not specifically limit the ratio between the specific compounds.

[0058] In a specific embodiment, the conductive material includes at least one of antimony-doped tin dioxide (ATO), fluorine-doped tin dioxide (FTO), tin-doped indium oxide (ITO), and carbon materials. When the conductive material includes at least one of the aforementioned substances, it can better cooperate and coordinate with the fluorinated solvent to further improve the conductivity of the protective layer, thereby enabling the lithium-ion battery to have higher cycle performance.

[0059] The carbon material in the present invention is preferably at least one of conductive carbon black, graphite, conductive polymer, multi-walled carbon nanotubes, graphene, and carbon fiber; wherein the conductive polymer is preferably polyaniline and / or polypyrrole.

[0060] The present invention does not specifically limit the type of the conductive polymer, which can be selected conventionally in the art. The present invention does not specifically limit the molecular weight of the conductive polymer.

[0061] When the conductive material is a mixture of the aforementioned multiple specific substances, the present invention does not specifically limit the ratio between the specific substances.

[0062] In a specific embodiment, the mass content k of the fluorinated solvent in the electrolyte is 5 to 30%. Within this range, it can better cooperate with the conductive particles, so that the shell and the core of the conductive particles have a good bonding strength, and at the same time, it can avoid the difficulty of lithium ion deintercalation caused by excessive fluorinated solvent content, so that the lithium ion battery has higher safety performance and cycle performance.

[0063] Illustratively, k is 5%, 10%, 15%, 20%, 25% or 30%.

[0064] In a specific embodiment, the mass content of the conductive particles in the protective layer 1 is 70-98wt%. Within this range, not only can the insulating effect of the protective layer 1 be ensured, and the safety of the battery can be improved, but also the positive electrode sheet can have a higher conductivity, which can effectively reduce the internal resistance of the battery, and make the battery have higher safety performance and cycle performance.

[0065] Exemplarily, the mass content of the conductive particles in the protective layer 1 is 70 wt %, 74 wt %, 78 wt %, 82 wt %, 86 wt %, 90 wt %, 94 wt % or 98 wt %.

[0066] In a specific embodiment, the average particle size b of the conductive particles is 0.05-1 μm. Within this range, the average particle size of the conductive particles is moderate, and energy loss will not be caused by excessively large particle sizes, nor will safety performance be reduced due to excessively small particle sizes.

[0067] Illustratively, b is 0.05 μm, 0.2 μm, 0.4, 0.6 μm, 0.8 μm or 1 μm.

[0068] In a specific embodiment, the mass content of the shell layer in the conductive particles is 2-40%; preferably, the mass content of the shell layer in the conductive particles is 10-30%. Within this range, not only the conductivity of the conductive particles can be guaranteed, but also the increase in internal resistance of the battery caused by the excessive thickness of the shell layer can be avoided, and the loss in the energy transmission process can be reduced.

[0069] Exemplarily, the mass content of the shell layer in the conductive particles is 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40%.

[0070] The mass content of the shell layer in the conductive particles in the present invention can be obtained by inductively coupled plasma (ICP) testing.

[0071] In a specific embodiment, the diaphragm includes a substrate, a glue layer and a ceramic layer; preferably, the ceramic layer is disposed on at least one side surface of the substrate, and the glue layer is disposed on a surface of the ceramic layer away from the substrate;

[0072] Preferably, the surface density p of the ceramic layer is 2 to 6 g / cm 3 .

[0073] The ceramic layer usually has a high melting point and good thermal conductivity. When the diaphragm contains a ceramic layer, it can cooperate with the protective layer 1 in the positive electrode sheet to provide double protection for the battery. It can effectively isolate the electrode material under high temperature conditions, reduce short circuits and thermal runaway caused by overheating, and further improve the safety performance of lithium-ion batteries.

[0074] The present invention does not specifically limit the materials of the substrate, adhesive layer and ceramic layer, and the commonly used materials in the field can be used. For example, the substrate can be selected from at least one of polypropylene, polyethylene, and polypropylene / polyethylene composite materials; the adhesive layer includes a polymer material, and the polymer material includes at least one of oily polyvinylidene fluoride, water-based polyvinylidene fluoride, oily polymethyl methacrylate, and water-based polymethyl methacrylate; the ceramic layer includes an inorganic material and a binder; wherein the inorganic material includes at least one of boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), titanium oxide (TiO2), zinc oxide (ZnO), cobalt oxide (CoO), magnesium hydroxide (Mg(OH)2), and silicon dioxide (SiO2); the binder can be consistent with the binder in the protective layer 1, and will not be repeated here.

[0075] Furthermore, when the surface density p of the ceramic layer is 2 to 6 g / cm 3 At the same time, it can further improve the thermal stability of the battery, provide stronger protection, and reduce the risk of internal short circuit caused by physical damage such as impact and extrusion during battery use.

[0076] For example, p is 2 g / cm 3 , 3g / cm 3 , 4g / cm 3 , 5g / cm 3 or 6g / cm 3 .

[0077] In a specific embodiment, the electrolyte further includes a lithium salt, and the lithium salt includes lithium hexafluorophosphate and lithium tetrafluoroborate;

[0078] Preferably, the total mass of lithium hexafluorophosphate and lithium tetrafluoroborate accounts for 8-20% of the electrolyte.

[0079] When mechanical abuse occurs, when the electrolyte contacts the negative electrode current collector, the lithium hexafluorophosphate in the electrolyte can react with the aluminum foil to form a dense and protective passivation film composed of aluminum fluoride on its surface. The passivation film has good chemical stability and can effectively isolate the aluminum foil from the external environment, preventing the aluminum foil from further direct contact with the electrolyte, acidic or alkaline substances and other substances that may cause corrosion, thereby improving the stability and corrosion resistance of the aluminum foil and the cycle performance of the battery. At the same time, lithium tetrafluoroborate can be adsorbed on the surface of the aluminum foil, changing its surface charge state and potential distribution, reducing the reactivity of the aluminum foil surface, and further reducing the occurrence of corrosion.

[0080] Therefore, when lithium-ion batteries are subjected to external mechanical forces such as heavy impact or needle puncture, the current collector may break or produce microcracks, thereby producing fresh cross-sections. The lithium hexafluorophosphate and lithium tetrafluoroborate in the electrolyte can quickly passivate the resulting cross-sections, reducing the occurrence of corrosion, thereby improving the safety and cycle performance of the battery.

[0081] Furthermore, when the mass content of lithium hexafluorophosphate and lithium tetrafluoroborate in the electrolyte is within the aforementioned range, they can work together better to further reduce the occurrence of corrosion during mechanical abuse, so that the battery has higher cycle performance and safety performance.

[0082] Illustratively, the total mass of lithium hexafluorophosphate and lithium tetrafluoroborate accounts for 8%, 10%, 12%, 14%, 16%, 18% or 20% of the electrolyte.

[0083] In a specific embodiment, the mass ratio of lithium hexafluorophosphate to lithium tetrafluoroborate is (10-145): 1. When the mass ratio of the two is within the aforementioned range, the two can better cooperate and synergize, further improving the safety performance and cycle performance of the battery.

[0084] Illustratively, the mass ratio is 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1, 100:1, 110:1, 120:1, 130:1, 140:1 or 145:1.

[0085] Furthermore, the thickness of the current collector, the thickness of the positive electrode active layer 2 and the thickness of the protective layer 1 in the lithium-ion battery have a great influence on the energy density, safety performance and cycle performance of the battery.

[0086] When the thickness of the current collector is too large, although it can prevent the battery from being punctured or broken when it is punctured, squeezed or impacted by heavy objects, thereby improving the safety performance of the battery, a current collector that is too thick will increase the internal resistance of the battery, affecting the discharge performance and cycle performance of the battery. It will also cause the pressure inside the battery to increase, increasing the risk of battery fire or even explosion, affecting the safety of the battery. If the current collector is too thin, the mechanical strength of the electrode will be significantly reduced, and the internal resistance of the battery will also increase, reducing the safety performance of the battery.

[0087] When the thickness of the positive electrode active layer 2 is too thick, the internal resistance of the battery will increase, affecting the output power and cycle life of the battery; at the same time, it will also cause excessive heat to be generated inside the battery during the charge and discharge process, and thermal runaway may occur. If it is too thin, the battery capacity will be significantly reduced, and it will be easily affected by stress during the charge and discharge process, affecting the cycle performance of the battery.

[0088] If the protective layer 1 is too thick, the energy density of the battery will be significantly reduced, and the internal resistance of the battery will be increased, thereby reducing the charging and discharging efficiency of the battery. If the protective layer 1 is too thin, it will not be able to play a protective role, thereby reducing the safety performance of the battery.

[0089] Therefore, it is necessary to control the thickness of the protective layer 1, the positive electrode active layer 2 and the positive electrode current collector 3 in the electrode sheet to achieve a balanced improvement in the electrochemical performance and safety performance of the lithium-ion battery.

[0090] In a specific embodiment, the thickness h1 of the protective layer 1 is 1-10 μm. Within this range, the safety performance of the lithium-ion battery can be improved accordingly, and the volume energy density loss is small.

[0091] Exemplarily, the thickness h1 of the protective layer 1 is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0092] In a specific embodiment, the thickness h2 of the positive electrode active layer 2 is 30-120 μm. Within this range, the battery energy density can be maximized while ensuring the battery safety performance.

[0093] Illustratively, the thickness h2 of the positive electrode active layer 2 is 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm or 120 μm.

[0094] In a specific embodiment, the thickness h3 of the positive electrode current collector 3 is 3-12 μm, which is beneficial to improving the toughness of the electrode sheet and the corrosion resistance of the current collector, and helps to improve the safety performance of the battery.

[0095] Illustratively, the thickness h3 of the positive electrode current collector 3 is 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm.

[0096] It should be noted that the thickness h1 of the protective layer 1 and the thickness h2 of the positive electrode active layer 2 in the present invention both refer to the thickness of one side located on one side of the positive electrode current collector 3 .

[0097] In a specific embodiment, the electrolyte further includes additives; the additives include at least one of vinylene carbonate, propylene sultone, methylene disulfonate, 1,3-propane sultone, vinyl sulfate, bis-succinonitrile, adiponitrile, glutaronitrile, hexane trinitrile, ethylene glycol bis(propionitrile) ether, glycerol trinitrile, tetravinylsilane, tris(trimethylsilyl)borate, hexamethyldisilazane, triphenyl phosphite, pentafluoroethoxycyclotriphosphazene, and 1,3,5-hexane trinitrile;

[0098] Preferably, the mass content of the additive in the electrolyte is 0.1-20%.

[0099] When the electrolyte includes the above additives, it helps the formation of SEI film and CEI film in the positive and negative electrodes, and improves the cycle performance of the battery.

[0100] When the additive is a mixture of the aforementioned multiple compounds, the present invention does not specifically limit the ratio between the specific compounds.

[0101] Furthermore, when the mass content of the additive in the electrolyte is within the above range, it can not only promote the formation of the interface film, but also avoid the increase in gas production and impedance caused by excessive content, so that the battery has higher cycle performance.

[0102] Exemplarily, the mass content of the additive in the electrolyte is 0.1%, 1%, 5%, 10%, 15% or 20%.

[0103] In a specific embodiment, the protective layer 1 further includes a binder;

[0104] The binder includes at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene and polyethylene oxide;

[0105] Preferably, the mass content of the binder in the protective layer 1 is 2-30 wt %.

[0106] When the protective layer 1 includes the aforementioned binder and the mass content of the binder in the protective layer 1 is within the aforementioned range, the bonding force between the protective layer 1 and the positive electrode current collector 3 and the positive electrode active layer 2 can be ensured, effectively preventing the protective layer 1 from falling off, which is beneficial to improving the safety performance of the battery.

[0107] Exemplarily, the mass percentage of the binder in the protective layer 1 is 2 wt %, 6 wt %, 10 wt %, 14 wt %, 18 wt %, 22 wt %, 26 wt % or 30 wt %.

[0108] When the binder is a mixture of the aforementioned multiple specific compounds, the present invention does not specifically limit the ratio between the specific compounds.

[0109] In a specific embodiment, the electrolyte also includes an organic solvent. Preferably, the organic solvent includes a carbonate solvent and / or a carboxylate solvent; preferably, the carbonate solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the carboxylate solvent includes at least one of ethyl acetate, ethyl propionate, propyl propionate, methyl propionate, methyl butyrate, and ethyl butyrate.

[0110] In a specific embodiment, the lithium salt may also include at least one of lithium difluorophosphate (LiPO2F2), lithium hexafluoroantimonate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethylsulfonyl imide (LiTFSI), lithium trifluoromethylsulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium, lithium difluorooxalatoborate (LiDFOB), lithium difluorobisoxalate phosphate, lithium bis(difluorophosphoryloxy)difluoroborate, and lithium tetrakis(difluorophosphoryloxy)borate.

[0111] In a specific embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector, and the negative electrode active layer includes a negative electrode active material.

[0112] The negative electrode current collector and the negative electrode active material in the present invention are not specifically limited, and may be materials commonly used in the art. For example, the negative electrode current collector may be copper foil, and the negative electrode active material may be artificial graphite.

[0113] The lithium-ion battery of the present invention is described in detail below through specific embodiments.

[0114] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0115] Example 1

[0116] 1) Preparation of positive electrode sheet: The positive electrode active material lithium cobalt oxide (LiCoO2), the conductive agent carbon black and carbon nanotubes (CNT), and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97.2:1:1:0.8, and then an appropriate amount of N-methylpyrrolidone (NMP) is added and stirred thoroughly until a uniform positive electrode active slurry is formed;

[0117] 95wt% of conductive particles and 5wt% of PVDF are mixed, NMP is added, and a protective layer slurry with a solid content of 40% is obtained after stirring; wherein the average particle size of the conductive particles is 0.5μm, the shell layer is fluorine-doped tin dioxide, the core is aluminum oxide, and the shell layer accounts for 20% of the mass content of the conductive particles;

[0118] The protective layer slurry is coated on two functional surfaces of the aluminum foil (thickness of 9 μm), and dried to obtain a pole piece coated with the protective layer; the positive electrode active slurry is then coated on the outer surface of the protective layer; after drying, rolling, and slitting, the positive electrode tabs are welded and protective adhesive tape is affixed to obtain a positive electrode sheet; wherein the single-side thickness of the protective layer is 3 μm, and the single-side thickness of the positive electrode active layer is 30 μm;

[0119] 2) Preparation of negative electrode sheet: artificial graphite, conductive carbon black, styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC) of negative electrode active materials are dispersed in an appropriate amount of deionized water at a mass fraction of 96.8:1.6:0.8:0.8, and after being fully stirred to form a uniform negative electrode slurry, the negative electrode slurry is evenly coated on the negative electrode current collector copper foil by a coating machine, and then dried, rolled, and cut to obtain a negative electrode sheet;

[0120] 3) Preparation of electrolyte: In a glove box filled with argon and with a water and oxygen content of less than 0.1ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP), and propyl propionate (PP) are mixed in a mass ratio of 10:20:20:20:30 to obtain a mixed organic solvent; then 14.5wt% of lithium hexafluorophosphate (LiPF6) and 0.5wt% of lithium tetrafluoroborate based on the total mass of the electrolyte are added, and 10wt% of fluoroethylene carbonate (FEC), 3wt% of 1,3-propane sultone (PS), 1wt% of 1,3,5-hexanetrinitrile (HTCN), 1wt% of adiponitrile (AND), and 1.5wt% of succinonitrile (SN) based on the total mass of the electrolyte are added, and after mixing evenly, the electrolyte is obtained after passing the moisture and colorimetry tests;

[0121] 4) Preparation of diaphragm: The diaphragm is composed of a substrate, a glue layer and a ceramic layer. The glue layer is located on one functional surface of the substrate, and the ceramic layer is located on another functional surface of the substrate. The substrate is polypropylene / polyethylene, the glue layer is oily polyvinylidene fluoride, and the ceramic layer includes inorganic particle aluminum oxide and binder polytetrafluoroethylene (mass ratio is 10:1). The surface density of the ceramic layer is 5g / cm 3 ;

[0122] 5) The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in sequence and prepared into a roll core by winding; the roll core is then wrapped with an aluminum-plastic film and injected with the above-mentioned electrolyte. After packaging, aging, formation, and secondary sealing, the lithium-ion battery of this embodiment is obtained.

[0123] Example 2

[0124] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass content of the fluorinated solvent in the electrolyte is 5%, and accordingly, the mass content of the mixed organic solvent in the electrolyte is increased.

[0125] Example 3

[0126] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 3), the fluorinated solvent also includes ethyl difluoroacetate, the total mass content of ethyl difluoroacetate and fluoroethylene carbonate in the electrolyte is 30%, and the mass ratio of ethyl difluoroacetate to fluoroethylene carbonate is 1:1; accordingly, the mass content of the mixed organic solvent in the electrolyte is reduced.

[0127] Example 4

[0128] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the average particle size of the conductive particles is 0.05 μm.

[0129] Example 5

[0130] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the average particle size of the conductive particles is 1 μm.

[0131] Example 6

[0132] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass content of the shell layer in the conductive particles is 10% of the conductive particles.

[0133] Example 7

[0134] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass content of the shell layer in the conductive particles is 30% of the conductive particles.

[0135] Example 8

[0136] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass content of the shell layer in the conductive particles is 2% of the conductive particles.

[0137] Example 9

[0138] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass content of the shell layer in the conductive particles is 40% of the conductive particles.

[0139] Example 10

[0140] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 1), the core of the conductive particles is zinc oxide, and the shell is antimony-doped tin dioxide;

[0141] In step 3), fluoroethylene carbonate is replaced by ethyl difluoroacetate.

[0142] Embodiment 11

[0143] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 1), the core of the conductive particles is boehmite and the shell is tin-doped indium oxide;

[0144] In step 3), fluoroethylene carbonate is replaced by methyl trifluoroethyl carbonate.

[0145] Example 12

[0146] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 1), the core of the conductive particles is cobalt oxide and the shell is graphite;

[0147] In step 3), fluoroethylene carbonate is replaced by p-difluorobenzene.

[0148] Embodiment 13

[0149] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 1), the shell layer is antimony-doped tin dioxide and fluorine-doped tin dioxide in a mass ratio of 1:1;

[0150] In step 4), the surface density of the ceramic layer is 2 g / cm 3 .

[0151] Embodiment 14

[0152] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 4), the surface density of the ceramic layer is 6 g / cm 3 .

[0153] Embodiment 15

[0154] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass content of lithium hexafluorophosphate in the electrolyte is 7.5%, the mass content of lithium tetrafluoroborate is 0.5%, and accordingly, the mass content of the mixed organic solvent in the electrolyte is increased.

[0155] Example 16

[0156] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass content of lithium hexafluorophosphate in the electrolyte is 19.5%, the mass content of lithium tetrafluoroborate is 0.15%, and accordingly, the mass content of the mixed organic solvent in the electrolyte is reduced.

[0157] Embodiment 17

[0158] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the thickness of one side of the protective layer is 1 μm.

[0159] Embodiment 18

[0160] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the thickness of one side of the protective layer is 10 μm.

[0161] Embodiment 19

[0162] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass content of the conductive particles in the protective layer is 70 wt%, and the mass content of PVDF is 5 wt%.

[0163] Embodiment 20

[0164] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass content of the conductive particles in the protective layer is 98 wt %, and the mass content of PVDF is 2 wt %.

[0165] Embodiment 21

[0166] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 3), the mass content of the additive 1,3-propane sultone in the electrolyte is 4%, the mass content of 1,3,5-hexane trinitrile is 4%, the mass content of adiponitrile is 2%, and the mass content of succinonitrile is 2%, and accordingly, the mass content of the mixed organic solvent in the electrolyte is reduced.

[0167] Embodiment 22

[0168] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 3), the mass content of the additive 1,3-propane sultone in the electrolyte is 6%, the mass content of 1,3,5-hexane trinitrile is 5%, the mass content of adiponitrile is 4%, and the mass content of succinonitrile is 4%, and accordingly, the mass content of the mixed organic solvent in the electrolyte is reduced.

[0169] Embodiment 23

[0170] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass content of fluoroethylene carbonate in the electrolyte is 4%, and the mass content of the mixed organic solvent in the electrolyte is increased accordingly.

[0171] Embodiment 24

[0172] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the average particle size of the conductive agent is 1.5 μm.

[0173] Embodiment 25

[0174] The preparation method of the lithium ion battery in this embodiment is basically the same as that in embodiment 1, except that in step 4), the surface density of the ceramic layer is 7 g / cm 3 .

[0175] Embodiment 26

[0176] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the diaphragm does not include a ceramic layer.

[0177] Embodiment 27

[0178] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the electrolyte does not include lithium tetrafluoroborate, and the mass content of lithium hexafluorophosphate in the electrolyte is 15%.

[0179] Embodiment 28

[0180] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass content of lithium hexafluorophosphate in the electrolyte is 21.3%, and the mass content of lithium tetrafluoroborate is 0.7%.

[0181] Embodiment 29

[0182] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the mass content of lithium hexafluorophosphate in the electrolyte is 14%, and the mass content of lithium tetrafluoroborate is 1%.

[0183] Embodiment 30

[0184] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the thickness of the protective layer is 12 μm.

[0185] Embodiment 31

[0186] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the electrolyte does not include additives 1,3-propane sultone, 1,3,5-hexane trinitrile, adiponitrile and succinonitrile, and accordingly, the mass content of the mixed organic solvent in the electrolyte is increased.

[0187] Embodiment 32

[0188] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that, in step 3), the mass content of the additive 1,3-propane sultone in the electrolyte is 8%, the mass content of 1,3,5-hexane trinitrile is 5%, the mass content of adiponitrile is 4%, and the mass content of succinonitrile is 4%, and accordingly, the mass content of the mixed organic solvent in the electrolyte is increased.

[0189] Embodiment 33

[0190] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 1, except that in step 1), the mass content of the conductive particles in the protective layer is 65%, and the mass content of PVDF is 35%.

[0191] Comparative Example 1

[0192] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 3, except that in step 1), the average particle size of the conductive particles is 0.05 μm.

[0193] Comparative Example 2

[0194] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 5, except that in step 3), the mass content of fluoroethylene carbonate in the electrolyte is 6%.

[0195] Comparative Example 3

[0196] The preparation method of the lithium ion battery in this embodiment is basically the same as that in Embodiment 5, except that in step 3), the electrolyte does not contain fluoroethylene carbonate, and the mass content of the mixed organic solvent in the electrolyte is increased accordingly.

[0197] Comparative Example 4

[0198] The preparation method of the lithium-ion battery in this embodiment is basically the same as that in Embodiment 5, except that in step 1), the positive electrode sheet does not contain a protective layer.

[0199] Test example

[0200] The lithium-ion batteries prepared in the above examples and comparative examples were tested for cycle performance and safety performance:

[0201] 1) Cycle performance

[0202] At an ambient temperature of 25°C, the lithium-ion battery is charged to 4.45V at a constant current of 1C, then charged at a rated voltage constant voltage until the cut-off current is 0.05C, and then discharged to 3.0V at 0.5C, and the initial discharge capacity is recorded as C0; the battery is cycled 1000 times according to the above-mentioned charge and discharge mechanism, and the discharge capacity after the cycle is recorded as C1, then the cycle capacity retention rate (%) = (C1 / C0) × 100%, and the calculation results are shown in Table 1.

[0203] 2) Heavy object impact

[0204] At an ambient temperature of 25°C, charge at a constant current and constant voltage of 0.5C to an upper voltage limit of 4.45V, with a cut-off current of 0.02C. Place the battery cell on the platform surface, and place a metal rod with a diameter of 15.8mm±0.2mm horizontally on the upper surface of the geometric center of the battery cell. Use a weight of 9.1kg±0.1kg to hit the surface of the battery cell with the metal rod in a free fall state from a height of 610mm±25mm, and observe for 6 hours. Each group of batteries tests 10 batteries. If there is no fire or explosion, the test is considered to have passed, otherwise it fails; record the number of batteries that passed out of the 10 batteries, for example, if 8 out of 10 batteries pass, it is recorded as 8 / 10PSS. The test results are shown in Table 1.

[0205] 3) Extrusion test

[0206] At an ambient temperature of 25°C, charge at a constant current and constant voltage of 0.5C to an upper limit voltage of 4.45V, and a cut-off current of 0.02C, at which point it is fully charged; place the wide side of the fully charged cell between two flat plates, and apply a squeezing force of 13.0kN±0.78kN between the plates, and stop once the pressure reaches the maximum value. Test 10 batteries in each group, and if there is no fire or explosion, the test is considered passed, otherwise it fails; record the number of batteries that pass out of the 10, for example, if 8 out of 10 batteries pass, it is recorded as 8 / 10PSS. The test results are shown in Table 1.

[0207] Table 1

[0208]

[0209]

[0210] From Table 1, we can see that:

[0211] Compared with Comparative Examples 1 to 4, the lithium-ion batteries in Examples 1 to 33 have higher cycle performance and safety performance, wherein the capacity retention rate of the lithium-ion battery in Example 3 after 1000 cycles can reach 83.0%, and the number of passes of the battery under heavy impact and compression is as high as 10 / 10PASS. It can be seen that the lithium-ion battery in the present invention can have both high safety performance and cycle performance.

[0212] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lithium-ion battery comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, characterized in that: The positive electrode sheet comprises a positive electrode current collector, a positive electrode active layer and a protective layer, wherein the protective layer is arranged on at least one side surface of the positive electrode current collector, and the positive electrode active layer is arranged on a surface of the protective layer away from the positive electrode current collector; The protective layer comprises conductive particles, wherein the conductive particles comprise a core and a shell disposed on at least a portion of the surface of the core, wherein the core comprises an inorganic material, and the shell comprises a conductive material; The electrolyte includes a fluorinated solvent; The lithium-ion battery satisfies 0.5≤b / k≤15, wherein b is the average particle size of the conductive particles, in μm, and k is the mass content of the fluorinated solvent in the electrolyte, in %.

2. The lithium-ion battery according to claim 1, characterized in that The fluorinated solvent includes at least one of fluoroethylene carbonate, ethyl monofluoroacetate, methyl difluoroacetate, ethyl difluoroacetate, methyl trifluoroethyl carbonate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, monofluorobenzene, 1,2-difluorobenzene, p-difluorobenzene, tris(2,2,2-trifluoroethyl) phosphate, bis(2,2,2-trifluoroethyl) phosphonate, 1,2-difluoroethylene, monofluoroethylene, and monofluoropropylene; And / or, the inorganic material includes at least one of aluminum oxide, magnesium oxide, titanium oxide, zinc oxide, silicon oxide, boehmite, and cobalt oxide; And / or, the conductive material includes at least one of antimony-doped tin dioxide, fluorine-doped tin dioxide, tin-doped indium oxide, and carbon material.

3. The lithium ion battery according to claim 1 or 2, characterized in that: The mass content k of the fluorinated solvent in the electrolyte is 5 to 30%; And / or, the mass content of the conductive particles in the protective layer is 70-98wt%.

4. The lithium ion battery according to any one of claims 1 to 3, characterized in that: The average particle size b of the conductive particles is 0.05-1 μm.

5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The mass content of the shell layer in the conductive particles is 2 to 40%; Preferably, the mass content of the shell layer in the conductive particles is 10-30%.

6. The lithium ion battery according to any one of claims 1 to 5, characterized in that: The diaphragm comprises a substrate, a glue layer and a ceramic layer; Preferably, the ceramic layer is disposed on at least one side surface of the substrate, and the adhesive layer is disposed on a surface of the ceramic layer away from the substrate; Preferably, the surface density p of the ceramic layer is 2 to 6 g / cm 3 .

7. The lithium ion battery according to any one of claims 1 to 6, characterized in that: The electrolyte also includes a lithium salt, and the lithium salt includes lithium hexafluorophosphate and lithium tetrafluoroborate; Preferably, the total mass of the lithium hexafluorophosphate and lithium tetrafluoroborate accounts for 8-20% of the electrolyte; Preferably, the mass ratio of lithium hexafluorophosphate to lithium tetrafluoroborate is (10-145):

1.

8. The lithium ion battery according to any one of claims 1 to 7, characterized in that: The thickness h1 of the protective layer is 1 to 10 μm, and / or the thickness h2 of the positive electrode active layer is 30 to 120 μm, and / or the thickness h3 of the positive electrode current collector is 3 to 12 μm.

9. The lithium ion battery according to any one of claims 1 to 8, characterized in that: The electrolyte also includes an additive; The additive comprises at least one of vinylene carbonate, propylene sultone, methylene methane disulfonate, 1,3-propane sultone, vinyl sulfate, bis-succinonitrile, adiponitrile, glutaronitrile, hexane trinitrile, ethylene glycol bis(propionitrile) ether, glycerol trinitrile, tetravinylsilane, tris(trimethylsilyl)borate, hexamethyldisilazane, triphenyl phosphite, pentafluoroethoxy cyclotriphosphazene, and 1,3,5-hexane trinitrile; Preferably, the mass content of the additive in the electrolyte is 0.1-20%.

10. The lithium ion battery according to any one of claims 1 to 9, characterized in that: The protective layer also includes a binder; The binder comprises at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene and polyethylene oxide; Preferably, the mass content of the binder in the protective layer is 2-30wt%.

Citation Information

Patent Citations

  • NEGATIVE ELECTRODE FOR LITHIUM METAL BATTERY, METHOD OF PREPARING NEGATIVE ELECTRODE, LITHIUM METAL BATTERY INCLUDING THE SAME, AND composite electrolyte

    CN108807851A

  • Current collector and electrode plate and electrochemical device comprising same

    CN115763825A

  • Electrochemical device and electronic device

    CN117043977A

  • Nonaqueous secondary battery, and method for manufacturing the same

    JP2012104422A

  • Negative electrode and battery employing the same

    TW202425380A